2022
DOI: 10.18494/sam4082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Deep Drawing Process for Micro Square Holes on Copper Sheets

Abstract: For the design and fabrication of dies by the deep drawing process, the problems of springback after load removal and the formation of cracks must be considered. In this study, a deep drawing process for micro square holes on copper sheets was analyzed on the basis of an updated Lagrangian formulation and 3D finite element analysis. Sheet behavior was simulated using a micro-elastoplastic material model, the performance of which was compared with that of models involving conventional materials. Subsequently, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Increasing the speed of the testing machine to 10 mm/min led to an increase in the maximum value of punch load to 3.75 KN for wax and 3.0 KN for grease, as presented in Figure (12). A comparable trend was observed when the speed increased to 15mm/min, which led to a rise in the maximum punch load to 4.0 KN for wax and 3.5 KN for grease, as shown in Figure (13). The higher punch load values recorded compared with grease indicate that lubricating with wax facilitates the pulling process and reduces the required force or the load applied for the pulling process.…”
Section: Effect Of Drawing Speedmentioning
confidence: 53%
See 1 more Smart Citation
“…Increasing the speed of the testing machine to 10 mm/min led to an increase in the maximum value of punch load to 3.75 KN for wax and 3.0 KN for grease, as presented in Figure (12). A comparable trend was observed when the speed increased to 15mm/min, which led to a rise in the maximum punch load to 4.0 KN for wax and 3.5 KN for grease, as shown in Figure (13). The higher punch load values recorded compared with grease indicate that lubricating with wax facilitates the pulling process and reduces the required force or the load applied for the pulling process.…”
Section: Effect Of Drawing Speedmentioning
confidence: 53%
“…Herein, the micro-deep drawing process on aluminum foil was chosen instead of the conventional deep drawing process because the micro-deep process forms a cup using a blank sheet of material between 0.001 to 0.300 mm thick, which is much thinner compared with that used in the conventional deep drawing (between 0.09 to 1.0 mm). In addition, the process of micro-deep drawing uses a punch between 1 and 9 mm in diameter, much smaller than that used in the conventional deep drawing (between 100 and 1000 mm) [11][12][13][14]. Several defects are often found in micro-deep drawings, such as earing on the cup edge, folding and wrinkling in the flange and cup wall, and tearing in the corner radius [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of trace elements added to Cu base should be controlled strictly in accordance with the bonding requirements; otherwise, it will have negative effects on the bonding properties of Cu alloy wire. Simultaneously, it was found that various degrees of cracks and fractures seem to happen to Cu alloy wires easily during the drawing process, which causes their low production efficiency and limits their applications in microelectronic packaging [90].…”
Section: Cu Alloy Wirementioning
confidence: 99%